Heart failure in persons with HIV: A scoping review - Maharaj, S.; Pillay, S. (SA Heart Journal, 2025)
Introduction: Human immunodeficiency virus (HIV) infection remains a global health challenge, marked by substantial morbidity and mortality. The introduction of antiretroviral therapy (ART) has dramatically extended life expectancy for people living with HIV (PLWH), but this increased longevity exposes them to long-term conditions such as cardiovascular diseases, particularly HIV associated cardiomyopathy leading to heart failure (HF). HF in PLWH is a rising cause of morbidity and mortality, yet remains poorly understood. This scoping review aims to systematically examine and synthesise the existing literature on the relationship between HIV and heart failure. Methods: The review followed the Arksey and O’Malley 6-stage methodological framework for scoping reviews. A systematic search was conducted using Boolean search strings across 4 databases: Scopus, Cochrane, PubMed, and ScienceDirect. The search was restricted to studies published between 2019 - 2023. Core articles yielded from data base search total 83. Twenty additional articles included in references do not form part of those yielded from Boolean string search. Total references 103. The results were analysed and synthesised to explore the prevalence, risk factors, and pathophysiology of heart failure in PLWH. Data analysis included descriptive statistics and thematic organisation. Results: The scoping review highlights a significant association between HIV and heart failure, with PLWH having a 2-fold increased risk of developing HF compared to HIV-negative individuals (p<0.001). Studies report a shift from heart failure with reduced ejection fraction (HFrEF) to heart failure with preserved ejection fraction (HFpEF) in aging PLWH populations on ART (p=0.05). Additionally, elevated N-terminal pro b-type natriuretic peptide (NT-proBNP) levels were consistently found in PLWH with low CD4 counts, suggesting a persistent inflammatory state affecting the heart (p=0.02). Other significant predictors of heart failure include high viral load (p=0.03), low CD4 counts (p=0.01), and traditional cardiovascular risk factors such as hypertension, diabetes, and dyslipidemia (p=0.001). Protease inhibitors and nucleoside reverse transcriptase inhibitors (NRTIs) were identified as ART classes associated with a higher cardiovascular risk (OR 1.8, 95% CI: 1.5-2.2). Conclusion: Heart failuare is an emerging clinical entity among PLWH, driven by both HIV-related and traditional cardiovascular risk factors. This review underscores the need for integrated cardiovascular management strategies that encompass regular cardiac monitoring, advanced diagnostic tools, and careful selection of ART regimens. Ongoing research is crucial to develop tailored prevention and management approaches for cardiovascular complications in PLWH, ensuring improved clinical outcomes and quality of life for this vulnerable population.